Capacity Analysis of Combined PLTD and Battery-Based PLTS in Supporting 24-Hour Electricity - Willy Novananda Siregar; Sasmoko Sasmoko; Kandhi Widodo; Rasman Rasman; Mimin Milasari (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Remote areas in Indonesia rely on diesel power plants with high costs, environmental impacts, and limited electricity access. Battery-based solar power offers a sustainable solution for 24-hour electricity while supporting digital economic growth. This study analyzes the combined capacity of PLTD and PLTS in providing continuous power in Sigapokna Village, Mentawai Islands. This study used comparative analysis methods, which compares conditions before and after PLTS operation. Results show that integration of 45 kW PLTD and 30 kWp PLTS increases customer operating hours from 7 hours to 10 hours per day, and planned PLTS expansion up to 170.8 kWp has potential to extend operating hours to 14 hours, even up to 24 hours with 319 kWp capacity. However, this capacity increase also impacts increased fuel oil consumption (BBM), demanding better energy efficiency strategies. These findings not only contribute to technical aspects of energy provision but also have significant implications for creative economy development and digital business in remote areas. Sustainable electricity access opens opportunities for Micro, Small, and Medium Enterprises (MSMEs) to utilize digital platforms, e-commerce, and digital financial services, while encouraging the birth of new digital-based energy business models (digital green business model) through Internet of Things (IoT) utilization, smart metering, and energy consumption data analysis. Thus, 24-hour electricity provision based on renewable energy not only improves community quality of life but also becomes a catalyst for digital economic transformation and social inclusion in Indonesia's 3T regions.